Development of innovative technology for processing secondary raw materials in the meat industry - Korotkiy, Igor Alekseevich; Nikolaevich Neverov, Evgeniy; Korotkaya, Elena Valerievna; Korotkih, Pavel Sergeevich (Nexo Revista Científica, 2022)
The slaughtered animals’ blood is a valuable secondary raw material in the meat industry. In this investigation, we propose a separation freezing technology for the blood, blood plasma and hemoglobin solution concentration. The processes of secondary meat raw materials separation freezing were studied for which the experiments for freezing in a capacitive crystallizer were conducted. The dependence of the freezing duration on the heat exchange surface temperature is determined and the cryoconcentration efficiency criterion is calculated. It is proved that the greatest freezing efficiency is observed at the heat exchange surface temperature of minus 2°C. At this temperature, the lowest dry matter loss was observed. The experiment in the separation freeze drying of a hemoglobin solution with the use of re-cryoconcentration was conducted. It is established that this technology can significantly reduce the dry matter loss. The pig blood plasma analysis before and after crystallization was conducted. It was found that crystallization has almost no effect on the amount and ratio of amino acids in the product.